An ex vivo evaluation of the sealing ability of polydimethylsiloxane-based root canal sealers - Preeti Jain; Varun Pruthi; Vimal K Sikri (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim was to study the sealing efficacy of polydimethylsiloxane-based root canal sealers. Materials and Methods: Polydimethylsiloxane-based root canal sealers were reviewed and subjected to an ex vivo study. A total of 60 extracted maxillary incisors were included in this study, which was conducted under two groups, Groups A and B, of 30 teeth each. In Group A, GuttaFlow and in Group B, RoekoSeal as sealers were used for obturation with Gutta-percha cones after preparing canal with a step back technique. The criterion for evaluating sealing efficacy of the sealers was light absorption by spectrophotometer. The collected data were analyzed statistically using one-way ANOVA test. Results: The findings of the study revealed that the mean leakage in Group B (0.1027) was significantly less than Group A (0.1649) (P < 0.001). RoekoSeal showed superior sealing ability. Conclusion: RoekoSeal had the better sealing ability than GuttaFlow and may be recommended for clinical use.